Uso de las Fuentes de Información en el Periodismo Político de los diarios Correo y La Industria de Trujillo, 2016 - Sáenz Crisóstomo, Maritza Manuela (2017)
The thesis describes the use of sources of information. Using the qualitative content analysis were studied a political news show public on two newspapers: Correo and La Industria of Trujillo to determine the treatment of information sources, Understanding that the treatment of information provided, depends of the qualifity of present information. was complemented with informal interviews to the editors of both media. Was cheking a bit of use the documental sources and specialized. Are prioritized the declarations of political actors that do not contrast with the rigor that merits. It was found that time is a factory to limit the posibilities of contrast to information. For that reason, the political journalists prefer the institutional sources because they are easier to access.